2015
DOI: 10.1021/acs.jpca.5b07071
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Study of the Thermochemical Properties of Organophosphorous Compounds

Abstract: Organophosphorous compounds are involved in many toxic compounds such as fungicides, pesticides, or chemical warfare nerve agents. The understanding of the decomposition chemistry of these compounds in the environment is largely limited by the scarcity of thermochemical data. Because of the high toxicity of many of these molecules, experimental determination of their thermochemical properties is very difficult. In this work, standard gas-phase thermodynamic data, i.e., enthalpies of formation (ΔfH298°), standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Out of the wealth of data on phosphorus‐based Benson groups reported by Glaude et al only two groups, C‐(H) 2 (C)(PO) and P(O)‐C 3 , are common with the current study. The CBS‐QB3 enthalpy, entropy, and heat capacity contributions reported by Glaude et al are, in respective order, −17 kJ mol −1 , 37 J K −1 mol −1 and 21 J K −1 mol −1 for C‐(H) 2 (C)(PO), and −289 kJ mol −1 , −8 J K −1 mol −1 and 48 J K −1 mol −1 for P(O)‐C 3 , in excellent agreement with the data in Table .…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Out of the wealth of data on phosphorus‐based Benson groups reported by Glaude et al only two groups, C‐(H) 2 (C)(PO) and P(O)‐C 3 , are common with the current study. The CBS‐QB3 enthalpy, entropy, and heat capacity contributions reported by Glaude et al are, in respective order, −17 kJ mol −1 , 37 J K −1 mol −1 and 21 J K −1 mol −1 for C‐(H) 2 (C)(PO), and −289 kJ mol −1 , −8 J K −1 mol −1 and 48 J K −1 mol −1 for P(O)‐C 3 , in excellent agreement with the data in Table .…”
Section: Resultsmentioning
confidence: 64%
“…For larger molecules, this is nowadays considered the best available alternative to obtain thermochemical properties with near chemical accuracy . The approach has in the past been used in the context of phosphorus compounds by Glaude et al and Dorofeeva and Moiseeva, who have reported values for roughly a 100 phosphorus‐based Benson groups.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic contains a large number of electrons (Z = 33) and the calculation methods used for the elements of the first rows for such thermochemical investigations in combustion (Khalfa et al, 2015;Lizardo-Huerta et al, 2018) are unsuitable. It is necessary to consider the relativistic effects due to the core electrons, which are generally described by pseudopotentials in the orbital bases.…”
Section: Methodsmentioning
confidence: 99%
“…This methodology has proven its precision with molecules containing hetero-atoms 15,16,24 . In addition, the low frequency vibration modes, corresponding to internal rotations, were treated as hindered rotors instead of harmonic oscillators, using THERMROT 25 .…”
Section: Methodsmentioning
confidence: 99%